Pedagogi Islam dan Nilai Nilai Humanis dalam Pendidikan Islam Kontemporer - M. Zainuddin Alanshori; Siti Suwaibatul Aslamiyah; Salman Zahidi (Akademika, 2025)
The reconstruction of Islamic pedagogic concepts and the integration of humanistic values in contemporary Islamic education is a strategic response to global challenges such as spiritual crises, social pressures, and moral decadence. This research aims to explore how Islamic pedagogic concepts can be reconstructed with an approach to the humanistic values of Islamic education in the contemporary era and what are the forms of integration of humanistic values in learning practices in Islamic educational institutions. The method used is Systematic Literature Review (SLR) This approach is also in accordance with the guidelines of Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA). The results of the study show that pedagogic approaches based on humanistic values, such as empathy, self-awareness, spirituality, and active participation, are able to present a learning space that is not only cognitive, but also touches the affective and moral dimensions of students. Thus, humanistic Islamic education is not only a bridge between tradition and modernity, but also a cultural and spiritual force in building a generation that is intelligent, moral, and ready to face the dynamics of the world wisely.